Determinants of academic achievement and its association with depression and anxiety among Palestinian secondary school students - Ahmead, Muna (Frontiers in Education, 2025)
BackgroundAfter 12th grade, the General Secondary Examination determines career paths and university eligibility. There is a lack of research on the association between depression, anxiety and academic achievement among 12th grade students in Palestine.MethodsThe current study aimed to assess the prevalence of depression and anxiety and their association with academic achievement among 12th grade students. The study utilized a cross-sectional research design. A self-reported questionnaire, including the Hospital Anxiety and Depression Scale (HADS), was used to gather data.ResultsA total of 1,083 students were recruited. Additionally, 27.3% of the students were experiencing depression, while 50.5% were experiencing anxiety. In comparison to other students, male students, those who attended government schools, resided in the southern region or the middle governorate, and had weak or moderate relationships with their teachers were less likely to achieve a high grade point average (GPA). However, students who resided in villages, had employed fathers or private employment, had mothers with higher education levels, were enrolled in the scientific stream, and were without anxiety were more likely to achieve a high GPA than other students.ConclusionThe findings of the current study may indicate the importance of educating students, parents, policymakers, and teachers about the effect of anxiety and sociodemographic variables on the academic achievement of students. Also, they highlight the importance of managing these factors to improve students' mental health and academic performance.